2020
DOI: 10.1111/1759-7714.13374
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA SNHG14 contributes to the progression of NSCLC through miR‐206/G6PD pathway

Abstract: Background: Previous studies have shown that the dysregulation of lncRNAs participates in non-small cell lung cancer (NSCLC) development. The purpose of this study was to research the biological function of lncRNA SNHG14 and its molecular mechanism in NSCLC progression. Methods: RT-PCR was applied for investigating the expression of SNHG14, miR-206 and G6PD. The progression of NSCLC was detected by CCK-8, Transwell and western blot assays. The targets of SNHG14 and miR-206 were measured by dual-luciferase repo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 22 publications
1
14
0
Order By: Relevance
“…Zhao et al indicated miR-206 inhibited cell viability, colony-forming ability and metastasis in NSCLC. 29 MiR-206 also participated in regulation in cancer progression under hypoxia. Tan et al unveiled miR-206 expression was downregulated in thyroid carcinoma tissues, cells and hypoxia-mediated thyroid carcinoma, and its inhibitor restrained the inhibition effects of nuclear paraspeckle assembly transcript 1 on hypoxia-mediated cell migration and invasion anaplastic thyroid carcinoma cells, 30 which meant that miR-206 suppressed cell migration and invasion under hypoxia.…”
Section: Discussionmentioning
confidence: 99%
“…Zhao et al indicated miR-206 inhibited cell viability, colony-forming ability and metastasis in NSCLC. 29 MiR-206 also participated in regulation in cancer progression under hypoxia. Tan et al unveiled miR-206 expression was downregulated in thyroid carcinoma tissues, cells and hypoxia-mediated thyroid carcinoma, and its inhibitor restrained the inhibition effects of nuclear paraspeckle assembly transcript 1 on hypoxia-mediated cell migration and invasion anaplastic thyroid carcinoma cells, 30 which meant that miR-206 suppressed cell migration and invasion under hypoxia.…”
Section: Discussionmentioning
confidence: 99%
“…Surveys such as that conducted by Zhao et al have shown that SNHG14 is highly expressed in non-small cell lung cancer cells. SNHG14 participates in the cell proliferation, invasion and migration of non-small cell lung cancer cells by regulating miR-206/G6PD [17]. As an oncogene in prostate cancer, SNHG14 contributes to the progression of prostate cancer by sponging miR-613 [18].…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism of miR-206 downregulated by BANCR was unclear. Several studies have reported that long non-coding RNA MIR4435-2HG, SNHG14 and LINC00707 can directly bind miR-206 to suppress it expression [26][27][28]. Therefore, we speculated BANCR decreased the miR-206 expression was involved in regulating these LncRNA expression.…”
Section: Discussionmentioning
confidence: 87%